The impact of the blue economy and renewable energy on CO2 emissions in Indonesia: An ARDL approach - Xenaneira Shodrokova; Anna Yulianita; Abdul Bashir; Imam Asngari; Ariodillah Hidayat (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2024)
Indonesia, the largest archipelagic country in the world with rich marine biodiversity, has significant potential for developing a blue economy encompassing aquaculture, sustainable fisheries, and maritime tourism. However, if not managed sustainably, these activities could increase CO2 emissions. Indonesia is also among the world's highest emitters of greenhouse gases, largely due to deforestation, forest burning for agriculture, and reliance on fossil fuels in the energy sector. Given global commitments to reducing emissions and mitigating climate change, this research explores how the blue economy and the transition to renewable energy can contribute to lowering CO2 emissions. This study examines both short- and long-term impacts using the Autoregressive Distributed Lag (ARDL) approach. The findings reveal that while increased aquaculture production initially reduces CO2 emissions due to efficiency gains and environmentally friendly technologies, its long-term effects are more complex and may lead to higher emissions. On the other hand, renewable energy consumption significantly reduces CO2 emissions in the short and long term. Conversely, higher energy intensity contributes to increased CO2 emissions, which can be mitigated through improved energy efficiency.